2014
DOI: 10.1186/1476-4598-13-155
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib treatment causes long-term testicular dysfunction in young male mice

Abstract: BackgroundWith increased long-term survivors of childhood cancer patients, therapy-associated infertility has become one of the most common late side-effects and significantly affects their life-quality. Therefore, evaluation of anti-cancer agents on male reproduction and infertility prevention are urgently demanding. The proteasome inhibitor bortezomib has been launched in clinical trials for childhood cancers, however, its potential side effects on reproduction have so far been neither investigated experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
(34 reference statements)
1
12
0
Order By: Relevance
“…There are many antioxidants that reduce the production of ROS (Dallak, 2019 As the literature investigated, a few studies were related to the damage of the bortezomib on the testes. One of them is about the bortezomib toxicity on testes presented on young mice (Hou et al, 2014). The other showed the bortezomib-induced testes damage via increasing the AMP-activated protein kinase (AMPK) level in murine Sertoli cells (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are many antioxidants that reduce the production of ROS (Dallak, 2019 As the literature investigated, a few studies were related to the damage of the bortezomib on the testes. One of them is about the bortezomib toxicity on testes presented on young mice (Hou et al, 2014). The other showed the bortezomib-induced testes damage via increasing the AMP-activated protein kinase (AMPK) level in murine Sertoli cells (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These results revealed that (1 → 3)-β-D-glucan and/or bortezomib treatment caused very serious structural defects in the testicular tissue that cause infertility due to breaking sperm maturation creating serious damage. Most of the previous studies also reported the testicular damage such as deformations in tubules, Leydig, and Sertoli cells due to chemotherapeutics (Hou et al, 2014;Karimi et al, 2018).…”
Section: Ta B L Ementioning
confidence: 98%
See 2 more Smart Citations
“…126 While little is known about the impact of biologic therapies, such as anti-20 monoclonal antibodies and proteasome inhibitors, on testicular function in humans, recent evidence in mice suggests that proteasome inhibitors may have longterm adverse effects on sperm concentrations, testicular weight, and Sertoli cell dysfunction, evidenced by persistently increased FSH levels. 127 Long-term studies in humans are needed, however, in order to delineate the effects of these therapies on future fertility.…”
mentioning
confidence: 99%